Δημόσιες επενδύσεις υποδομής: ο ρόλος τους στην οικονομική συμπεριφορά και την κερδοφορία του αγροτικού τομέα στην Ελλάδα - Φουσέκης, Παναγιώτης; Παπακωνσταντίνου, Ασπασία (SPOUDAI Journal of Economics and Business, 2000)
This paper uses a restricted profit maximization framework to investigate the influence of public infrastructure on the behavior and the economic performance of the Agricultural Sector in Greece. The empirical application for the period 1974-95 shows that: a) Changes in the stock of public infrastructure have important consequences for the output supply and the demand for private inputs; b) Increases in this public input work towards higher profitability in the sector. The increase in profit, however, has been, at the margin, lower than the market price of this input. This implies that the stock of public infrastructure has been higher than the optimum. JEL Classification: Q11, Q12